2012
DOI: 10.1590/s0100-204x2012000800003
|View full text |Cite
|
Sign up to set email alerts
|

Adubação nitrogenada no consórcio de milho com duas espécies de braquiária em sistema plantio direto

Abstract: O objetivo deste trabalho foi avaliar a produtividade de grãos e de forragem do consórcio entre milho e espécies de braquiária (safras de 2008/2009 e 2009/2010), submetidos a doses de nitrogênio em cobertura, em sistema plantio direto. Utilizou-se o delineamento experimental inteiramente casualizado, com quatro repetições, em arranjo fatorial 2x5, com duas espécies de braquiária (Urochloa brizantha 'Xaraés' e U. ruziziensis) e cinco doses de N aplicadas em cobertura: 0, 50, 100, 150 e 200 kg ha‑1. Foram avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
49
4
35

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 21 publications
11
49
4
35
Order By: Relevance
“…The dry matter production observed in this experiment was below the 4,000 kg ha -1 of dry matter reported by Costa et al (2012), for Urochloa ruziziensis and maize intercropping. However, Batista et al (2011) reported Urochloa ruziziensis dry matter of about 1,000 kg ha -1 , at the maize physiological maturity, for regions of the São Paulo State.…”
Section: Resultscontrasting
confidence: 78%
“…The dry matter production observed in this experiment was below the 4,000 kg ha -1 of dry matter reported by Costa et al (2012), for Urochloa ruziziensis and maize intercropping. However, Batista et al (2011) reported Urochloa ruziziensis dry matter of about 1,000 kg ha -1 , at the maize physiological maturity, for regions of the São Paulo State.…”
Section: Resultscontrasting
confidence: 78%
“…In some current production systems, with the adoption of more modern hybrids, irrigation, and NTS, the recommended nitrogen level in topdressing is much higher. In a study conducted by Costa et al (2012a) nitrogen fertilization in topdressing was evaluated in corn intercropped with tropical forages of the same region and under very similar conditions to those seen in this study; 200 kg N ha -1 resulted in the highest crop production level.…”
Section: Resultsmentioning
confidence: 65%
“…The corn crop is highly dependent on the use of fertilizers to ensure high yields, which and nitrogen (N) is the most required nutrient (COSTA et al, 2012a). However, in corn production systems, the need for fertilizers is known as one of the factors that increases the production costs (COSTA et al, 2012b); in addition, its misuse can cause environmental harm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations